Postpartum Bone Mineral Density in Women Treated for Thromboprophylaxis with Unfractionated Heparin or LMW Heparin - Pettilä, Ville; Leinonen, Pekka; Markkola, Antti; Hiilesmaa, Vilho; Kaaja, Risto (Thrombosis and Haemostasis, 2002)
Venous thromboembolism remains an important cause of maternal mortality. In a randomised open study, 44 pregnant women with confirmed previous or current thromboembolism were randomised to receive either low-molecular-weight heparin, dalteparin (N = 21) once daily subcutaneously or unfractionated sodium heparin (UF heparin, N = 23) twice daily subcutaneously for thromboprophylaxis during pregnancy and puerperium. Bone mineral density (BMD) in the lumbosacral spine was measured with dual X-ray absorptiometry (DEXA) 1, 6, 16, 52 weeks and, if possible, 3 years after delivery. BMD values were also compared with those of healthy, delivered women (N =19).Mean BMD of the lumbar spine was significantly lower in the unfractionated heparin group compared with the dalteparin and with the control groups (repeated measures ANOVA p = 0.02). BMD in the dalteparin group did not differ from BMD of healthy delivered women. Multiple logistic regression analysis revealed that therapy was the only independent factor influencing BMD at weeks 16 and 52. Therefore we recommend use of dalteparin instead of UF heparin for long-term thromboprophylaxis during and after pregnancy.
Keywords: Bone mineral density; osteoporosis; pregnancy; heparin; dalteparin